Evaluation of the Effect of Axial Length on Foveal Microstructure: A Comparative Optical Coherence Tomography Angiography Study - Kahramanoglu, Fatih; Alyamaç Sukgen, Emine; Albayrak, Muzaffer Talha (Scientific Reports in Medicine, 2025)
Objective: Myopia, characterized by an increase in the eye’s axial length, is a common refractive error that can lead to degenerative changes in the retina and optic nerve. The purpose of this study was to evaluate the effects of different axial length (AL) values on retinal and optic nerve head structures using Optical Coherence Tomography (OCT) and Optical Coherence Tomography Angiography (OCT-A). Method: This prospective cross-sectional study, included 150 patients (150 eyes) with cataracts, aged between 18 and 69 were. Patients were divided into five groups based on their AL values. Following ophthalmological examination, retinal nerve fibre layer (RNFL) and ganglion cell complex (GCC+IPL) thicknesses were measured with OCT, while foveal and peripapillary vascular density were measured with OCT-A. The obtained data were statistically compared among the AL groups. Results: The study revealed a significant thinning of RNFL and GCC+IPL thicknesses as AL increased (p<0.05). This thinning was particularly prominent in the nasal and inferior quadrants of the RNFL, and in the infero-nasal and superotemporal quadrants of the GCC+IPL. In vascular density measurements, an increase in superficial and deep foveal density (SFD and DFD) values was observed as AL increased (p<0.05). This is thought to be due to the optical magnification effect caused the increade in axial length. No significant correlation was found between foveal avascular zone (FAZ) area and AL. Our findings supported that increasing axial length lead to thinning of neural tissue thicknesses of the retina and optic nerve, and this condition was associated with mechanical stress...